Pengembangan alat kompres panas untuk mengatasi kelemahan otot ekstremitas bawah pada lansia dengan degeneratif muskuloskeletal - Supril Junaidi; Rr Sri Endang Pujiastuti; Nina Indriyawati (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: Musculoskeletal disorders in the elderly with degenerative diseases experience decreased muscle strength in the lower extremities, resulting in decreased mobility and quality of life. Non-pharmacological interventions such as heat-based reflexology and range of motion (ROM) exercises can improve circulation and muscle strength. Purpose: To compare the effectiveness of range of motion (ROM) exercises and heat-based reflexology in improving lower limb muscle mobility in the elderly. Method: A quasi-experimental study using a two-group pre-posttest design involving elderly participants from the Prolanis program was conducted. The first group performed range of motion (ROM) exercises, while the second group received heat-based reflexology applied at 39-40°C for 15-20 minutes. Data were analyzed using linear regression and independent t-tests. Results: Parameter estimation analysis showed that range of motion (ROM) exercises resulted in greater improvements in muscle mobility compared to heat-based reflexology. The regression coefficient for the ROM group was B = –0.153; 95% CI = –0.282–0.025; p = 0.020, indicating a significantly lower effect on improving muscle mobility compared to the ROM group. However, heat-based reflexology compression contributed to muscle relaxation, improved blood circulation, and physical comfort among elderly participants. Conclusion: Range of motion (ROM) exercises and heat-based reflexology compression both improved muscle mobility in elderly participants, but ROM exercises were more effective. Therefore, ROM is recommended as the primary intervention, while heat compression is used as a supportive therapy to enhance the effectiveness of the exercises. Keywords: Elderly; Heat-Based Reflexology Massage Compress; Musculoskeletal Degenerative; Muscle Weakness; Range Of Motion (ROM).